Laboratory study of the influence of changing the injection rate on P-wave velocities and water saturation in a Limestone - Lopes, Sofia; Lebedev, Maxim (CSIRO, 2012)
Forced imbibition was performed in a Limestone Savonnieres by injecting water into a dry sample. The injection was monitored with X-ray Computed Tomography (CT) and active ultrasonic measurements so that the time-space distribution of the invading fluid could be simultaneously observed in CT images and quantified through measuring P-wave velocities and water saturation. The CT scans allowed us to observe a water front advancing away from the area of injection and estimate saturation. Through the evolution of P-wave velocities, we observed a strong influence on the acoustic response with the presence of water and with the changing of injection rates. The approaching of the water front to the monitored position decreased P-wave velocities while the saturation increased continuously. The P-wave velocities decrease occurred for a short period of time and was followed by a sharp increase which happens when the fluid front crossed the monitored position. Decreasing injection rate decreased P-wave velocities and saturation. Increasing injection rate, increased P-wave velocities and saturation, sharply and for a short period of time followed by a slight decrease for P-wave velocities and a continuous increase. Our experimental data confirms how sensitive acoustic waves are to the presence of water and that changing injection rates promote considerable fluid distribution that is drastically reflected in the acoustic velocities.